Speciality of decision making choice in retail market of finance services - Vytautas Sūdžius (Business: Theory and Practice, 2007)
The complicated client behaviour, especially during the decision-making process, causes problems to business specialists working in finance sector. That makes one to look for a theoretical basis and carry out surveys in order to explain the factors influencing the client when making a decision about buying finance services. The objective of this research is to identify possible applications of factors and their interaction. In order to achieve the set target, the following tasks had to be solved: to analyse the main concepts about client’s decision-making process in finance sector; overview and systematize factors and make new classification; to create theoretical model identifying all key factors, taking into consideration specific Lithuanian finance market features and local environmental, economical and social circumstances; to estimate and analyze the output results in order to indicate possible applications of the above mentioned factors. This research indicates the main factors and groups of factors influencing decision making of clients: different value and features of various finance services, role of internal and external marketing complex and situational factors. Results of survey also let us identify means how to improve finance services and the methods they are provided to retail market.